2012
DOI: 10.1002/bdd.1813
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CYP isozymes involved in benzbromarone metabolism in human liver microsomes

Abstract: Benzbromarone (BBR) is metabolized to 1'-hydroxy BBR and 6-hydroxy BBR in the liver. 6-Hydroxy BBR is further metabolized to 5,6-dihydroxy BBR. The aim of this study was to identify the CYP isozymes involved in the metabolism of BBR to 1'-hydroxy BBR and 6-hydroxy BBR and in the metabolism of 6-hydroxy BBR to 5,6-dihydroxy BBR in human liver microsomes. Among 11 recombinant P450 isozymes examined, CYP3A4 showed the highest formation rate of 1'-hydroxy BBR. The formation rate of 1'-hydroxy BBR significantly cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…This result is consistent with the previous reports that CYP2C9 and CYP2C19 are the major isozymes capable of catalyzing the formation of 6-OH-BBR (McDonald and Rettie, 2007;Kobayashi et al, 2012). CYP2C9 was also responsible for the formation of DBH from BBR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the previous reports that CYP2C9 and CYP2C19 are the major isozymes capable of catalyzing the formation of 6-OH-BBR (McDonald and Rettie, 2007;Kobayashi et al, 2012). CYP2C9 was also responsible for the formation of DBH from BBR.…”
Section: Discussionsupporting
confidence: 93%
“…Early metabolic studies identified that the major metabolites of BBR are 6-hydroxybenzbromarone (6-OH-BBR) formed by cytochrome P450 isoforms CYP2C9 and CYP2C19, and 1ʹ-hydroxybenzbromarone (1ʹ-OH-BBR) produced by CYP3A4 (McDonald and Rettie, 2007;Kobayashi et al, 2012). It has been reported that human hepatocarcinoma HepG2 cells infected with adenovirus vector expressing CYP2C9 significantly increase the cytotoxicity of BBR, suggesting that CYP2C9 is associated with BBR-induced cytotoxicity (Iwamura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Due to reports of fatal hepatotoxicity, benzbromarone was withdrawn from the market by one of its main manufacturers, though it is still available from other drug companies in several countries across the globe [87, 94]. Genetics could be a factor that influences toxicity risk.…”
Section: ) Drugs That Inhibit the Reabsorption Of Uric Acid: Uricosumentioning
confidence: 99%
“…Genetics could be a factor that influences toxicity risk. Benzbromarone is metabolized by CYP2C9 to form the active metabolite 6-hydroxybenzbromarone (which has inhibitory activity upon URAT1 uric acid uptake) and by CYP3A4 to form 1′-hydroxybenzbromarone [75, 87, 94, 95]. 6-hydroxybenzbromarone is further metabolized to 5,6-dihydroxybenzbromarone by CYP2C9 and CYP1A2 [94].…”
Section: ) Drugs That Inhibit the Reabsorption Of Uric Acid: Uricosumentioning
confidence: 99%
See 1 more Smart Citation